Fungicide resistance in Botrytis cinerea and identification of Botrytis species associated with blueberry in Michigan - Abbey, Joel A.; Alzohairy, Safa A.; Neugebauer, Kerri A.; Hatlen, Ross J.; Miles, Timothy D. (Frontiers in Microbiology, 2024)
Botrytis blossom blight and fruit rot, caused by Botrytis cinerea, is a significant threat to blueberries, potentially resulting in substantial economic losses if not effectively managed. Despite the recommendation of various cultural and chemical practices to control this pathogen, there are widespread reports of fungicide resistance, leading to decreased efficacy. This study aimed to characterize the resistance profile of B. cinerea isolated from blighted blossoms and fruit in 2019, 2020 and 2022 (n = 131, 40, and 37 for the respective years). Eight fungicides (fludioxonil, thiabendazole, pyraclostrobin, boscalid, fluopyram, fenhexamid, iprodione, and cyprodinil) were tested using conidial germination at specific discriminatory doses. Additionally, 86 isolates were phylogenetically characterized using the internal transcribed spacer regions (ITS) and the protein coding genes: glyceraldehyde-3-phosphate dehydrogenase (G3PDH), heat-shock protein 60 (HSP60), and RNA polymerase II second largest subunit (RPB2). This revealed higher fungicide resistance frequencies in 2020 and 2022 compared to 2019. Over all three years, over 80% of the isolates were sensitive to fludioxonil, fluopyram, and fenhexamid. Pyraclostrobin and boscalid showed the lowest sensitivity frequencies (<50%). While multi-fungicide resistance was observed in all the years, none of the isolates demonstrated simultaneous resistance to all tested fungicides. Botrytis cinerea was the most prevalent species among the isolates (74) with intraspecific diversity detected by the genes. Two isolates were found to be closely related to B. fabiopsis, B. galanthina, and B. caroliniana and 10 isolates appeared to be an undescribed species. This study reports the discovery of a potentially new species sympatric with B. cinerea on blueberries in Michigan.